Ochrona zdrowia w publicznym systemie finansowym - Łyszczarz, Błażej; Hnatyszyn-Dzikowska, Anna (Healthcare in the System of Public Finance, 2009)
Though the last decades are characterized by changes towards marketizing of public sector, public fends are still the predominant source of healthcare financing worldwide. The first part of the paper presents models of public financing of healthcare. The subsequent parts present the trends in public financing of healthcare in Poland focusing on the results of introducing the social health insurance in 1999, as well as discuss these trends in a broader international perspective
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 166-173